Deconstructing Dr. Strangelove : the secret history of nuclear war films - Maloney, Sean M., 1967- (Potomac Books, an imprint of the University of Nebraska Press, 2020)
"'Deconstructing Dr. Strangelove' examines how well the Cold War crisis films stack up against historical reality, or at least as much of that reality as we can reconstruct with confidence"--